EU-Turkey negotiations: Still in the "Cyprus impasse" - Heinz Kramer (Stiftung Wissenschaft und Politik (SWP), 2007)
At a meeting held in Brussels on 14-15 December 2006, the European Council confirmed the decision reached by the General Affairs Council (i.e. EU foreign ministers) on 11 December to provisionally suspend eight chapters from the accession negotiations with Turkey. That decision was prompted by Turkey's continuing refusal to also apply to Cyprus the additional protocol to the agreement on the EU-Turkey Customs Union, which was adopted in summer 2005 and intended to expand the agreement to cover all the new Member States that acceded to the Union on 1 May 2004. In practice, the issue concerns opening up Turkish ports and airports to ships and aircraft of the Republic of Cyprus. However, Turkey's government, led by Prime Minister Recep Tayyip Erdogan, is only prepared to do this if direct trade between the EU and the breakaway 'Turkish Republic of Northern Cyprus' is also enabled, as promised by the EU back in April 2004. However, such a step is being blocked within the Union by the new EU Member State Cyprus. The decision reached by the Council in December was unable to resolve this conflict
Keywords: 320